Promoters and Barriers to Implementation of Tracheal Intubation Airway Safety Bundle: A Mixed-Method Analysis*. Issue 10 (October 2017) - Finn Davis, Katherine; Napolitano, Natalie; Li, Simon; Buffman, Hayley; Rehder, Kyle; Pinto, Matthew; Nett, Sholeen; Jarvis, J. Dean; Kamat, Pradip; Sanders, Ronald C.; Turner, David A.; Sullivan, Janice E.; et al.
Abstract : Objectives: To describe promoters and barriers to implementation of an airway safety quality improvement bundle from the perspective of interdisciplinary frontline clinicians and ICU quality improvement leaders. Design: Mixed methods. Setting: Thirteen PICUs of the National Emergency Airway Registry for Children network. Intervention: Remote or on-site focus groups with interdisciplinary ICU staff. Two semistructured interviews with ICU quality improvement leaders with quantitative and qualitative data-based feedbacks. Measurements and Main Results: Bundle implementation success (compliance) was defined as greater than or equal to 80% use for tracheal intubations for 3 consecutive months. ICUs were classified as early or late adopters. Focus group discussions concentrated on safety concerns and promoters and barriers to bundle implementation. Initial semistructured quality improvement leader interviews assessed implementation tactics and provided recommendations. Follow-up interviews assessed degree of acceptance and changes made after initial interview. Transcripts were thematically analyzed and contrasted by early versus late adopters. Median duration to achieve success was 502 days (interquartile range, 182–781). Five sites were early (median, 153 d; interquartile range, 146–267) and eight sites were late adopters (median, 783 d; interquartile range, 773–845). Focus groups identified common "promoter" themes—interdisciplinary approach, influential champions, and quality improvement bundle customization—and "barrier" themes—time constraints, competing paperwork and quality improvement activities, and poor engagement. Semistructured interviews with quality improvement leaders identified effective and ineffective tactics implemented by early and late adopters. Effective tactics included interdisciplinary quality improvement team involvement (early adopter: 5/5, 100% vs late adopter: 3/8, 38%; p = 0.08); ineffective tactics included physician-only rollouts, lack of interdisciplinary education, lack of data feedback to frontline clinicians, and misconception of bundle as research instead of quality improvement intervention. Conclusions: Implementation of an airway safety quality improvement bundle with high compliance takes a long time across diverse ICUs. Both early and late adopters identified similar promoter and barrier themes. Early adopter sites customized the quality improvement bundle and had an interdisciplinary quality improvement team approach. Abstract : Supplemental Digital Content is available in the text.